2016
DOI: 10.1371/journal.pone.0149795
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Xenon Inhibition in a Cationic Pentameric Ligand-Gated Ion Channel

Abstract: GLIC receptor is a bacterial pentameric ligand-gated ion channel whose action is inhibited by xenon. Xenon has been used in clinical practice as a potent gaseous anaesthetic for decades, but the molecular mechanism of interactions with its integral membrane receptor targets remains poorly understood. Here we characterize by X-ray crystallography the xenon-binding sites within both the open and “locally-closed” (inactive) conformations of GLIC. Major binding sites of xenon, which differ between the two conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 75 publications
(98 reference statements)
2
31
1
Order By: Relevance
“…6B), and the outer-interfacial sites (gray spheres, Fig. 6B) (61). Finally, xenon also occupies the 9′ pore site in locally closed GLIC (gray sphere, Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…6B), and the outer-interfacial sites (gray spheres, Fig. 6B) (61). Finally, xenon also occupies the 9′ pore site in locally closed GLIC (gray sphere, Fig.…”
Section: Discussionmentioning
confidence: 93%
“…6B) (41) or xenon in locally closed GLIC (gray sphere, Fig. 6B) (61). Additional binding sites for xenon in locally closed GLIC are located at the intrasubunit general anesthetic binding site (blue sphere, Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, soaking anesthetics into pLGIC crystals also requires a delicate balance between permeation of sufficient anesthetics into the crystals and potential disruption of the crystal lattice. Non-traditional soaking methods have proved successful for incorporating anesthetics into pLGICs, including adding saturated volatile desflurane to the reservoir well after GLIC crystals are observed (Nury et al, 2011) and pressuring xenon into GLIC crystals in a gas chamber (Sauguet, Fourati, Prange, Delarue, & Colloc’h, 2016). …”
Section: Crystallization Of Plgics In the Absence And Presence Of Genmentioning
confidence: 99%
“…Anomalous signals from xenon, bromide or selenium atoms, if they exist in the chosen anesthetics or anesthetic analogs, will also boost the certainty of the assignment of anesthetics. Xenon (Sauguet et al, 2016), 2-bromoethanol (Q. Chen et al, 2017; Sauguet, Howard, et al, 2013), bromoform (Laurent et al, 2016; Spurny et al, 2013), and brominated or seleniated barbiturates (Fourati et al, 2017) have all been successfully identified based on anomalous signals.…”
Section: Crystallization Of Plgics In the Absence And Presence Of Genmentioning
confidence: 99%